Negros en Argentina: integración e identidad - Jean Arsène Yao (Amnis)
This paper analyses the construction of Argentinian identity in the nineteenth century, partially built on the negation of Black people in the country. Therefore, it explains the sociocultural resistance of Afro-Argentinians, a community fighting for its own specificity and existence.